2017
DOI: 10.1016/j.electacta.2017.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Reductive dechlorination of trichloroacetic acid (TCAA) by electrochemical process over Pd-In/Al2O3 catalyst

Abstract: A B S T R A C TElectrochemical reduction treatment was found to be a promising method for dechlorination of Trichloroacetic acid (TCAA), and acceleration of electron transfer or enhancement of the concentration of atomic H* significantly improve the electrochemical dechlorination process. Bimetallic Pd-based catalysts have the unique property of simultaneously catalyzing the production of atomic H* and reducing target pollutants. Herein, a bimetallic Pd-In electrocatalyst with atomic ratio of 1:1 was evenly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 41 publications
(47 reference statements)
1
26
1
Order By: Relevance
“…As was observed in other studies, the reductive dechlorination of TCAA and DCAA was relatively rapid but the reduction of MCAA to acetic acid was quite slow and deemed to proceed via the indirect reduction of MCAA by atomic H* generated at Pd nuclei formed on the electrode surface. The acceleration of the EC reduction of HAAs by atomic H* was also observed in another study [29] which utilized an EC-controlled bimetallic Pd/In catalyst that promoted the formation of atomic H*. The catalyst was incorporated into an EC reactor whose operations resulted in a rapid removal of TCAA yet MCAA again was observed to form as a final product.…”
Section: Effects Of Ec Conditions and Electrode Materials On The Ec Rsupporting
confidence: 55%
“…As was observed in other studies, the reductive dechlorination of TCAA and DCAA was relatively rapid but the reduction of MCAA to acetic acid was quite slow and deemed to proceed via the indirect reduction of MCAA by atomic H* generated at Pd nuclei formed on the electrode surface. The acceleration of the EC reduction of HAAs by atomic H* was also observed in another study [29] which utilized an EC-controlled bimetallic Pd/In catalyst that promoted the formation of atomic H*. The catalyst was incorporated into an EC reactor whose operations resulted in a rapid removal of TCAA yet MCAA again was observed to form as a final product.…”
Section: Effects Of Ec Conditions and Electrode Materials On The Ec Rsupporting
confidence: 55%
“…The synergistic effect of metals can upgrade the activity and selectivity of catalysts and relieve catalyst aging and loss. 197 Experimental parameters (e.g., pH value, applied current, electrolyte) also impact the performance of cathodes heavily. 185,198,199 Take the cathode potential as an example, Jiang et al 199 found that the applied potential had a great influence on the evolution of three different hydrogen species, namely adsorbed atomic hydrogen (H* ads ), absorbed atomic hydrogen (H* abs ), and molecular hydrogen (H 2 ).…”
Section: Pd-based Catalystsmentioning
confidence: 99%
“…However, it should be noted that there is still lacking of fundamental principles for interpreting the dehalogenation mechanism of a typical HOP without experimental examination due to that fact that there are many unexpected observations related to the mechanisms mentioned above. 187,195,197,212,215 For instance, Liu et al 197 found that atomic H* ads formation function and the electron transfer process both existed in the trichloroacetic acid (TCAA) removal process, while the enhanced indirect atomic H* ads reduction process played a principal role in the degradation process ( Fig. 11).…”
Section: Electroreductive Dehalogenation Mechanismsmentioning
confidence: 99%
“…Indirect atomic hydrogen reduction, i. e., the electrocatalytic hydro‐dechlorination, is another effective strategy for the electroreductive dehalogenation of organic chlorides, where atomic hydrogen species is produced on the catalyst surface and acts as a strong reductant for triggering the C−Cl bonds breaking reaction (shown in Figure a) …”
Section: Mechanisms For the Electroreductive Dehalogenationmentioning
confidence: 99%
“…Due to the costly materials used and the intriguing catalytic properties of nanomaterials, electrocatalysis on shape‐controlled noble metal nanoparticles has received an increasing attention for the reductive dehalogenation over the past several years, e. g., For instance, the Pd NPs loaded on different supporting materials exhibit remarkable electrocatalytic hydro‐dechlorination performances for the various aryl chlorides including chlorophenols and chlorophenoxyacetic acids, where the exposed (111) facets was considered to be highly active for triggering the reductive dechlorination reactions …”
Section: Critical Factors For Controlling the Electroreductive Dehalomentioning
confidence: 99%